2018
DOI: 10.1097/gme.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge about menopause and hormone therapy in middle-aged Brazilian women: a population-based household survey

Abstract: The knowledge about menopause and HT demonstrated by the interviewees was low and possibly related to the time of exposure to qualified information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
5
13
0
Order By: Relevance
“…Improved knowledge may result in receipt of early intervention for vaginal atrophy, which is in line with previously published health-care advice 5 . Indeed, results from other studies in Brazil support such an approach [20][21][22] . For instance, de Arruda Amaral et al 20 reported a smaller analysis of a larger, cross-sectional study involving middle-aged women in the Metropolitan Region of Campinas 20,21,[23][24][25][26][27] , showing that the enrolled women may have had limited knowledge of the menopause and hormone therapy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Improved knowledge may result in receipt of early intervention for vaginal atrophy, which is in line with previously published health-care advice 5 . Indeed, results from other studies in Brazil support such an approach [20][21][22] . For instance, de Arruda Amaral et al 20 reported a smaller analysis of a larger, cross-sectional study involving middle-aged women in the Metropolitan Region of Campinas 20,21,[23][24][25][26][27] , showing that the enrolled women may have had limited knowledge of the menopause and hormone therapy.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, results from other studies in Brazil support such an approach [20][21][22] . For instance, de Arruda Amaral et al 20 reported a smaller analysis of a larger, cross-sectional study involving middle-aged women in the Metropolitan Region of Campinas 20,21,[23][24][25][26][27] , showing that the enrolled women may have had limited knowledge of the menopause and hormone therapy. The authors concluded that adequate dissemination of knowledge by clinicians would help inform women and enable them to participate in shared decisionmaking, allowing them to choose the best form of therapy for their symptoms 20 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…showed that among 40–45-year-old women from Iran there was a meaningful relation between women’s knowledge, so that higher educated, employed and satisfied women had higher knowledge of menopause [ 11 ]. Data from Brazilian women, aged 45–60 years, confirmed that higher education level was significantly associated with a higher knowledge on menopause [ 12 ]. A study of 44 Turkish women (with a mean age of 50.41 ± 6.36 years) living in the district centre of Beylikova and having mostly a lower educational level showed positive changes in menopause-related level of knowledge after a planned training programme [ 13 ].…”
Section: Discussionmentioning
confidence: 99%